Age and Early Graft Function Relate With Risk-Benefit Ratio of Allogenic Islet Transplantation Under Antithymocyte Globulin-Mycophenolate Mofetil-Tacrolimus Immune Suppression. Issue 9 (September 2017) - Lee, Dae Hae; Keymeulen, Bart; Hilbrands, Robert; Ling, Zhidong; Van de Velde, Ursule; Jacobs-Tulleneers-Thevissen, Daniel; Maleux, Geert; Lapauw, Bruno; Crenier, Laurent; De Block, Christophe; Mathieu, Chantal; Pipeleers, Daniel; et al.
Abstract : Background: Induction therapy with a T cell–depleting agent followed by mycophenolate mofetil and tacrolimus is presently the most frequently used immune suppression (IS) regimen in islet transplantation. This study assesses its safety and tolerability in nonuremic type 1 diabetic recipients. Methods: Fifty-one patients (age, between 29 and 63 years) with high glycemic variability and problematic hypoglycemia received intraportal islet grafts under anti-thymocyte globulin-mycophenolate mofetil-tacrolimus protocol. They were followed up for over 48 months for function of the implant and adverse events. Results: Severe hypoglycemia and diabetic ketoacidosis were absent in patients with functioning graft. Immune suppressive therapy was maintained for 48 months in 29 recipients with sustained function (group A), whereas 16 patients stopped earlier due to graft failure (group B) and in 6 for other reasons. Group A was significantly older at the time of implantation and achieved higher graft function at posttransplantation month 6 under similar dose of IS. Prevalence of IS-related side effects was similar in groups A and B, occurring predominantly during the first year posttransplantation. IS-related serious adverse events (SAE) were reported in 47% of patients, with 4 presenting with cytomegalovirus infection and 4 (age, 42-59 years) diagnosed with cancer. Except in 1 patient with cancer, all SAEs resolved after appropriate treatment. Conclusions: These risk/benefit data serve as a basis for clinical decision-making before entering an intraportal islet transplantation protocol. A longer benefit is observed in recipients of higher age (≥40 years), but it is not associated with more side effects and SAE. Abstract : Intra-portal islet transplantation using ATG in combination with MMF-Tac is safe and tolerable in nonuremic type 1 diabetic recipients and a longer benefit is observed in recipients of higher age (≥40 yrs) without more side effects and serious adverse events.